Intelligence Phase sebagai Dasar Proses Pembuatan Keputusan untuk Membangun Model Aplikasi DSS Pada UKM - Pelawi, Dewan (Bina Nusantara University, 2013)
Decision making is a process of choosing an alternative action used for a specific purpose or goal that has been set. Managerial decision-making involves data and information from entire business process. Data and information are procesesed to support decision-making. The purpose of this paper is to get a statement of goals, problems and data of the UKM Gerak Tani. The Method to be used is inteliggence phase which is the first stage of the four stages of decision making according to Herbert A Simon. It includes several activities aimed to identify problem situations or opportunities such as finding the problem classification, problem decompositionand problem ownership. The expected results of this research are the purpose documentation of the organization, searching and scanning procedures, data collection, identification of issues, ownership issues, classification issues and problem statement.